Linking Stakeholder Salience to Sustainability Accountability in the Telecom Sector: The Case of Kenya’s Safaricom - Ogoro, Ombati Thomas; Hirschsohn, Philip (Contemporary Research in Business, Management and Economics Vol. 6, 2024)
Organizations have an obligation not only to create wealth for their shareholders, but also to address wider stakeholder issues that are not necessarily of economic value. As organizations face stiff pressure from various stakeholders. To achieve this, environmental and social concerns are considered as pertinent issues to attain sustainability. This study investigates how stakeholder salience, based on stakeholder power, legitimacy and urgency impacts on Sustainable Supply Chain Management (SSCM) practices. The study adopts a case study design, focusing on Safaricom, one of Africa’s most innovative telecommunication firms. This in-depth case study solicited data from management and selected stakeholders, including communities, telecoms regulators, corporate customers, and suppliers to represent different salience levels. The study used semi-structured interview protocols to solicit data which was analyzed using content analysis. The findings revealed that the more attributes a stakeholder has, the more attention they receive and consequently the greater their influence on Safaricom’s SSCM practices. In order to effectively manage stakeholder expectations, Safaricom managers needed to determine which should be prioritized while sustaining the firm’s bottom line. Future research should be done on stakeholder salience, SSCM practices and TBL performance outcomes in diverse socio-economic contexts to explore the impact of various stakeholder interests on the cellular industry. There is also need for further study on stakeholder salience, SSCM practices and TBL performance outcomes in the food sector in Africa.